Meningkatkan Pelayanan Informasi Orang Tua Siswa SMAN 1 Ciwaru Dengan Menerapkan Framework Dynamic CRM - Inri Purwaningrum; Hendri Irawan; Humisar Hasugian; Lauw Li Hin (Asosiasi Pendidikan Tinggi Informatika dan Komputer Provinsi DKI Jakarta, 2023)
Maintaining good relations with parents of students is important for the school. SMA Negeri 1 Ciwaru is a public school that requires the contribution of student parents to support the school administration process. in this case SMA Negeri 1 Ciwaru has problems in maintaining relationships with student guardians, such as the absence of information services that can be accessed directly by student guardians so that misscommunication often occurs with the school. In addition, there is no information on student progress in academic or non-academic, and there are no facilities to submit criticism and suggestions for schools so it is difficult for schools to improve services. Based on the existing problems, this study uses a Customer Relationship Management (CRM) approach strategy which includes one CRM stage, namely Enhance by implementing a dynamic CRM framework which contains a series of stages in implementing a CRM. Data collection methods in this study using direct observation, interviews and documentation. This research produces an e-CRM system that can improve information services that is built using the Hypertext Preprocessor (PHP) programming as the programming language and the MySQL database as the database. The final product of this system is an information service for parents of SMA Negeri 1 Ciwaru students which includes announcement features, circulars, academic information, lists of grades, making grade reports, information reports, reports of criticism and suggestions, as well as other needs that help smooth business processes and communication for both parties